SOOT PARTICLE TRAJECTORIES OF A DI DIESEL ENGINE AT 18° ATDC CRANKSHAFT ANGLE - Mohd Hafidzal, Mohd Hanafi; Wan Mohd Faizal, Wan Mahmood; Muhammad Zaidan, Abdul Manaf; Mohamad Shukri , Zakaria; Mohd Noor Asril, Saadun; Mohd Nur Azmi, Nordin (IOP SCIENCE, 2013)
Among the major pollutants of diesel engine is soot. Soot is formed as an unwelcomed product in combustion system. Soot emission to the atmosphere leads to air global warming and health problem. Furthermore, deposition of soot particle on cylinder wall contaminates lubricant oil hence increases its viscosity. This reduces durability of lubricant oil, causing pumpability problems and increasing wear. Therefore, it is necessary to study soot formation and its movement in diesel engines. This study focuses on soot particle trajectories in diesel engine by considering diameter of soot particles that were formed at 18° ATDC crankshaft angle. These soot particle movement are under the influence of drag force with different radial, axial and angular settings and simulated by using MATLAB routine. Mathematical algorithm which was used in the MATLAB routine is trilinear interpolation and 4th order of Runge Kutta. Simulation was carried out for a combustion system of 4 valves DI diesel engine from inlet valve closing (IVC) to exhaust valve opening (EVO). The results show that small diameter of soot particles were transferred near the cylinder wall while bigger soot particle mostly moved in inner radius of the combustion chamber.